REDESIGN OF RESIDENTIAL DRAINAGE SYSTEM IN BEKASI CITY - Nurrochmat, Muhammad; UK, Olvi Pamadya; Susilowati, Susilowati; Anggitasari, Inge (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Margahayu Housing, located in Bekasi City, is one of the flood-prone residential areas that frequently experiences inundation during the rainy season, disrupting residents’ daily activities. This study aims to determine the design flood discharge and redesign the drainage channel dimensions to accommodate runoff effectively. The research was conducted through several stages involving primary and secondary data collection, hydrological and hydraulic analyses, and hydraulic modeling using the HEC-RAS software. The hydrological analysis applied the Log Pearson Type III method to determine rainfall distribution, while the Rational Method was used to calculate the design flood discharge based on rainfall data from three stations: Halim, Teluk Pucung, and Bendung Cikarang. The calculated design discharge values were: S1 = 0.376 m³/s, S2 = 1.147 m³/s, S3 = 1.124 m³/s, S4 = 0.273 m³/s, S5 = 0.430 m³/s, and S6 = 0.336 m³/s. The comparison between the existing flow capacity (Qcap) and the design discharge (Qs) indicated that several drainage channels were inadequate to accommodate flood flow. Therefore, a redesign was performed by enlarging the channel cross-sections. The proposed new dimensions for channels S1, S2, S3, and S6 are 1.4 meters in height and 1.2 meters in base width. Validation through HEC-RAS modeling confirmed that the redesigned channels can safely convey the design flood discharge. This study demonstrates that appropriate hydrological and hydraulic modeling plays a crucial role in effective flood mitigation planning for urban drainage systems.